2013
DOI: 10.1371/journal.pone.0078710
|View full text |Cite
|
Sign up to set email alerts
|

Red-Backed Vole Brain Promotes Highly Efficient In Vitro Amplification of Abnormal Prion Protein from Macaque and Human Brains Infected with Variant Creutzfeldt-Jakob Disease Agent

Abstract: Rapid antemortem tests to detect individuals with transmissible spongiform encephalopathies (TSE) would contribute to public health. We investigated a technique known as protein misfolding cyclic amplification (PMCA) to amplify abnormal prion protein (PrPTSE) from highly diluted variant Creutzfeldt-Jakob disease (vCJD)-infected human and macaque brain homogenates, seeking to improve the rapid detection of PrPTSE in tissues and blood. Macaque vCJD PrPTSE did not amplify using normal macaque brain homogenate as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The sample is subjected to cycles of incubation and sonication during which PrP TSE converts normal prion protein into new PrP TSE . In previous studies we have shown that normal red‐backed vole brain homogenate expressing prion protein with serine/serine (S/S) at Codon 170 is an efficient substrate for amplification of PrP TSE from vCJD‐infected macaque brain . Figure A shows Western blot results of PMCA‐generated PrP TSE from 10 −9 to 10 −11 duplicate dilutions of vCJD‐infected macaque brain homogenate in normal human plasma (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample is subjected to cycles of incubation and sonication during which PrP TSE converts normal prion protein into new PrP TSE . In previous studies we have shown that normal red‐backed vole brain homogenate expressing prion protein with serine/serine (S/S) at Codon 170 is an efficient substrate for amplification of PrP TSE from vCJD‐infected macaque brain . Figure A shows Western blot results of PMCA‐generated PrP TSE from 10 −9 to 10 −11 duplicate dilutions of vCJD‐infected macaque brain homogenate in normal human plasma (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All supernatants were discarded and all liquid was carefully removed. The pellets were thoroughly resuspended with 100 μL of 10% red‐backed vole brain homogenates with 170S/S genotype . Duplicate samples were then subjected to protein misfolding cyclic amplification (PMCA) as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…As the PrP res amounts in brains have not been reported in previous studies, and as animal models suggest that prion levels in plasma are much lower than those in whole blood or WBCs, it remains unclear whether our PMCA methods can be used to detect blood‐borne prions in vCJD patients. It is possible that higher detection sensitivity can be achieved by changing the substrate to red‐backed vole brain …”
Section: Discussionmentioning
confidence: 99%
“…Quaking‐induced conversion and its improved versions, in which agitation induced PrP amyloid formation, were reported to detect prion from cerebrospinal fluids and nasal brushing of sporadic CJD patients . In PMCA, protease resistant isoform of PrP (PrP res ), along with infectivity, are very efficiently propagated by repeating sonication and incubation with, if necessary, an addition of seed‐dependent cofactors or using a specific substrate . Recently, PMCA was shown to detect PrP Sc in white blood cells (WBCs) from a vCJD patient .…”
mentioning
confidence: 99%
“…We first proved the existence of PrP Sc in the CSF and blood of BSE-infected macaques by PMCA, and showed that cynomolgus macaque BSE PrP Sc , and non-macaque PrP C , effectively converted mouse PrP C to a proteinase K (PK)-resistant form. It is well known that PMCA of several xenogeneic combinations of PrP Sc seed and PrP C substrate can overcome the species barrier (Kurt et al, 2007(Kurt et al, , 2011Green et al, 2008;Castilla et al, 2008;Yoshioka et al, 2011;Murayama et al, 2012;Nemecek et al, 2013), despite the divergent amino acid sequence of prion proteins. Since the BSE prion was transmissive to ICR (WT) mice (Masujin et al, 2008), the cynomolgus macaque PrP Sc generated by the cross-species transmission of BSE prion may retain the original characteristics of BSE PrP Sc , including structural compatibility with mouse PrP C and DSP dependency in PMCA reactions.…”
Section: Discussionmentioning
confidence: 99%